Crucial role of dendritic cells in the generation of anti-tumor T-cell responses and immunogenic tumor microenvironment to suppress tumor development - Tominaga, Moe; Uto, Tomofumi; Fukaya, Tomohiro; Mitoma, Shuya; Riethmacher, Dieter; Umekita, Kunihiko; Yamashita, Yoshihiro; Sato, Katsuaki (Frontiers in Immunology, 2024)
Dendritic cells (DCs) are known as a unique professional antigen (Ag)-presenting cells (APCs) to prime naïve T cells for the initiation of adaptive immunity. While DCs are believed to play a pivotal role in generating anti-tumor T-cell responses, the importance of DCs in the protection from the progression of tumor remains elusive. Here, we show how the constitutive deficiency of CD11chi DCs influences the progression of tumor with use of binary transgenic mice with constitutive loss of CD11chi DCs. Constitutive loss of CD11chi DCs not only enhances the progression of tumor but also reduces the responses of Ag-specific T cells. Furthermore, the congenital deficiency of CD11chi DCs generates the immunosuppressive tumor microenvironment (TME) that correlated with the marked accumulation of myeloid-derived suppressor cells (MDSCs) and the prominent productions of the immunosuppressive mediators. Thus, our findings suggest that CD11chi DCs are crucial for generating anti-tumor T-cell responses and immunogenic TME to suppress the development of tumor.